Differences in Driving Behavior Between Professional and Nonprofessional Drivers - Machado, Mariana Sebastião; Agra, Cândido da; Cardoso, Carla Sofia (Sociologia: Revista da Faculdade de Letras da Universidade do Porto, 2026)
Research has been highlighting possible behavioral differences between professional and nonprofessional drivers, beyond their distinct involvement in accidents. This study explores these differences in a sample of 560 professional and nonprofessional Portuguese drivers, using a self-reported survey on driving behaviors and accident history. Results showed i) that nonprofessional drivers presented more aggressive driving behaviors; ii) the existence of a positive association between aggressive driving behaviors and road accidents only in the nonprofessional drivers; iii) no group differences regarding prosocial driving behaviors, although professional drivers reported significantly more prosocial driving behaviors than aggressive. The study's results, and limitations are discussed. https://doi.org/10.21747/08723419/soc53a2